Wheelchair Athletes and Their Considerations in Sporting Activities - Abdullah, Nagoor Meera; Tumijan, Wahidah; Appukutty, Mahenderan (Universitas Negeri Semarang, 2011)
Wheelchair athletes need to engage into physical activity and sports in order to keep their body functioning for activity for daily living (ADL) or for sporting actions. Sports also are a part of the rehabilitation program since it been introduced by Sir Ludwig Gutmann in England late 1940s. With the growth of sport activity in daily lives of persons with disabilities, it has been rightly perceived that disabled persons could obtain the same physical and emotional benefits from sport as their able-bodied counterparts, leading to an increased need to overcome limitations, opponents and records. The introduction of sports therapy in rehabilitation, as well as further involvement in sports depends on the severity of the injury, might lead a disabled person to either become a non-competitive athlete or a paralympic athlete. Athletes with Spinal cord injury facing problems with their thermoregulatory response. In relation to that, during exercise in the heat, paraplegic athletes demonstrates similar increase in core temperature compared with able-bodied athletes, but at a much lower metabolic rate, reflecting the decreased heat dissipation. Individuals who use wheelchairs vary widely in their level of cardiorespiratory fitness, some being seriously unfit and others are achieving levels that compare closely with those of fit able-bodied athletes. Wheelchair users also should be encouraged to use a hand-propelled rather than a motorized chair in daily life and to eat a diet that is well regulated to avoid accumulation of excess body fat.